Optimizing AI's Role in Advancing Interior Design Industry - Lesmana, Vania Azalia Audrey; Tina, Antonetta; Retno Yanti, Sugesti (Universitas Atma Jaya Yogyakarta, 2024)
The digital era encourages using artificial intelligence (AI) in various industries, including interior design and architecture. Growth in AI usage is projected to increase by 34% in 2023-2032. AI can improve efficiency, productivity, and decision-making in the design process. With AI, designers can optimise visualisation, space layout, material, and colour selection and predict customer preferences. AI saves time and costs and results in innovative solutions per client requirements. As it evolves, AI improvises technologies to assist designers such as DALL-E, Blender, AI Dungeon, Spline, and CogniCAS. However, the adoption of AI in interior design and business management in Indonesia still needs improvement. This study analysed related articles from 2019 to 2023 using Publish or Perish and VOSviewer visualisation to investigate the optimal utilisation of AI in supporting the interior design process. This research aims to provide practical insights and recommendations for interior designers, students, and practitioners adopting AI solutions to improve performance and competitiveness and develop a standard framework for AI technology platforms.